2022
DOI: 10.3389/fpsyt.2022.924431
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Reginal Homogeneity in Left Anterior Cingulum Cortex and Precentral Gyrus as a Potential Neuroimaging Biomarker for First-Episode Major Depressive Disorder

Abstract: ObjectiveThere is no objective method to diagnose major depressive disorder (MDD). This study explored the neuroimaging biomarkers using the support vector machine (SVM) method for the diagnosis of MDD.Methods52 MDD patients and 45 healthy controls (HCs) were involved in resting-state functional magnetic resonance imaging (rs-fMRI) scanning. Imaging data were analyzed with the regional homogeneity (ReHo) and SVM methods.ResultsCompared with HCs, MDD patients showed increased ReHo in the left anterior cingulum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
(41 reference statements)
1
7
1
Order By: Relevance
“…The SVM method has been diffusely applied in disease diagnosis for neuropsychosis ( 15 , 18 , 20 ). Running the LIBSVM 3 software package in MATLAB, the SVM methodology was used to test the sensitivity, accuracy, and effectiveness of using DC values identified in abnormal brain regions to distinguish MDD from HCs (detailed information can be found in Supplementary Material ).…”
Section: Methodsmentioning
confidence: 99%
“…The SVM method has been diffusely applied in disease diagnosis for neuropsychosis ( 15 , 18 , 20 ). Running the LIBSVM 3 software package in MATLAB, the SVM methodology was used to test the sensitivity, accuracy, and effectiveness of using DC values identified in abnormal brain regions to distinguish MDD from HCs (detailed information can be found in Supplementary Material ).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, patients imaged during an acute psychotic episode exhibited increased ReHo in the medial/lateral prefrontal cortex, anterior insula, and putamen and these findings were interpreted as evidence for increased local connectivity ( Wang et al, 2018 , 2016 ; Xiao et al, 2017 ; Xu et al, 2015 ). Similarly, higher ReHo values were reported in the left superior frontal gyrus and left inferior temporal gyrus in early-onset Parkinson’s disease ( Sheng et al, 2016 ), left anterior cingulum cortex in major depressive disorder patients ( Song et al, 2022 ), right superior temporal gyrus and bilateral hippocampus, parahippocampus, fusiform gyrus and cerebellum in patients with obsessive–compulsive disorder ( Yan et al, 2022 ), in right superior and inferior frontal gyrus in depressive patients compared to non-depressive patients ( Fang et al, 2021 ). The lower ReHo signal in frontal and temporal lobes in patients with schizophrenia, Alzheimer’s disease, and mild cognitive impairment were associated with a lower working memory performance and other cognitive abilities ( Han et al, 2011 ; Zhang et al, 2012 ) and lower ReHo in the right putamen in early-onset PD compared to late-onset ( Sheng et al, 2016 ).…”
Section: Discussionmentioning
confidence: 75%
“…Decreased ReHo values were observed in the left precentral gyrus and were positively correlated with EPQ-N scores and negatively correlated with EPQ-L scores in the patients. Reduced ReHo values of the left precentral gyrus in patients with MDD have been found in the published literature (Zhang et al, 2021;Song et al, 2022). Previous studies have shown that patients with MDD who attempted suicide had fewer hemodynamic responses in the left precentral gyrus than patients with MDD without suicidal ideation and HCs (Tsujii et al, 2017).…”
Section: Discussionmentioning
confidence: 86%